Rancang Bangun Generator Turbin Angin Axial Flux Permanent Magnet (AFPM) Neodymium dengan Stator berbahan Fiberglass - Anas Noor Firdaus; Kusdinar, Afriana; Fauzhan, Alif Paraj; Wibowo, Yuni Ari (Yayasan Literasi Sains Indonesia, 2024)
Alternative energy are need for the energy crisis that has occurred recently, one of the efforts to create alternative energy is by using wind, the energy obtained from the wind is converted into a generator. In general, generators produce voltage at quite high rpm, and also require exciter current for the trigger current to produce voltage. The aim of this research is to design a generator to obtain a constant voltage with low rotation, so a low speed generator is needed, namely the Axial Flux Permanent Magnet (AFPM) Generator. Methods and design results. The generator is made in the form of a single stator, single rotor. The generator stator is designed using fiberglass as a holder for 9 coils, while the rotor is designed in a disk shape using iron as a holder for the Neodymium N52 iron boron permanent magnet, totaling 9 slots and 12 poles, each slot consisting of 125 coils with a diameter of 0.6 mm, can work at revolutions per minute above 300, the faster the better and a maximum of 1200 rpm, the generator frame is also made using a main motor housing. Based on the objectives, methods and design results, the generator created can produce a voltage of 6 volts at a maximum rotation of 1500 rpm when tested in a low speed wind column of less than 14 m/s